Current Trends and Recent Development of Transdermal Drug Delivery System TDDS - Soni, Devbrat; Prakash, Kartikay; Shakeel, Kashif; Kesharawani, Priyanka (Asian Journal of Pharmaceutical Research and Development, 2023)
The basic goal of TDDS is to administer medications at a predefined pace into systemic circulation through the skin with little inter- and intrapatient variance. TDDS come in a variety of forms, including reservoir and matrix systems, single-layer drugs in adhesive, and multi-layer drugs in adhesive. With more than 35 items already authorised for sale in the US and around 16 active components authorised for use as TDDSs internationally, the market value of TDDS products is growing quickly. Due to its low likelihood of patient rejection, simplicity of administration, and patients' convenience and perseverance, a transdermal drug delivery system [TDDS] is a desirable substitute for traditional needle injections. However, transdermal administration is complicated and constrained by the physicochemical characteristics of the skin. The many types of TDDS approaches that are now accessible are covered in this study, along with their individual benefits and drawbacks, characterization techniques, and potential. A transdermal patch is an tenacious medical patch that's applied to the skin to administer a particular quantum of drug via the skin and into the bloodstream, constantly accelerating the mending of a damaged body part. Transdermal medicine administration is a fairly new technology that has the implicit to reduce the need for needles when furnishing a wide range of specifics, but the cost is an essential element to take into account.